Phytochemical analysis and antibacterial activity of Anisophylliea disticha extracts - Sahena, Ferdosh (2017)
Anisophyllea disticha has been utilized as traditional medicine to cure diseases such as diarrhea, dysentery, fever, and jaundice. The objectives of this study was to screen the phytochemicals present in A. disticha and to determine the bioactive compounds of A. disticha by using GC-MS. Roots, stems, and leaves of A. disticha were extracted by Soxhlet extraction using two solvents, methanol, and hexane. Methanol extraction gave a high yield of crude extract compared to hexane extraction. Crude extract from methanol extraction was further used for qualitative phytochemical analysis. Saponin, phenol, tannin and flavonoid were present in the root, stem, and leaves of A. disticha. The steroid was only identified in root and stem of A. disticha. Terpenoid and alkaloid both were absent in roots, stems and leaves of A. disticha. Bioactive compounds of A. disticha were identified by GC-MS. The root of A. disticha consists high amount of Benzenepropanoic acid, 3, 5-bis (1, 1-dimethylethyl)-4-hydroxy-, methylester, followed by 1, 2-Octadecanediol, 1-Nonadecene, 3",8,8"-Trimethoxy-3- Piperidyl-2,2"-binaphthalane-1,1",4,4"-tetrone and 2-Hexadecanol. 1-Octadecanol, behenic alcohol, and 1-Hexadecanol, was major compounds identified in the stem of A. disticha. The leaves of A. disticha was consists mainly 1,6 - Methanonaphthalene-1(2H)-ol,octahydro-4,8a,9,9-tetramethyl-(1a,4β,4aα,6β,8aα) / Patchoulic alcohol, Ethanol, 2-(9-Octadecenyloxy)-(Z), and Hexadecanoic acid, methyl ester / Palauytic ester . Based on antimicrobial assay by disc diffusion method (200, 400 and 600 µg/disc), leaf extracted using methanol exhibited potent growth inhibitory activity against Staphylococcus epidermidis with a diameter of 7.67±0.58 mm.The presence of bioactive compounds of A. disticha proves the potential to treat bacterial diseases.